2012
DOI: 10.3109/13561820.2012.736889
|View full text |Cite
|
Sign up to set email alerts
|

Theories, relationships and interprofessionalism: Learning to weave

Abstract: In this article, we illustrate the application of a number of theoretical frameworks we have used to guide our work in interprofessional education (IPE) and collaborative interprofessional care (IPC). Although we do not claim to be experts in any one of these theories, each has offered important insights that have broadened our understanding of the complexities of interprofessional learning and practice. We have gained an appreciation for an increasing number of theories relevant to IPE and IPC, and, as a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
0
22
1
Order By: Relevance
“…Thus, if they are to promote effective collaboration, the collaborating professionals should aim to have greater focus on the same idea rather than their particular professions (Hall & Weaver, 2001;Hall, Weaver, & Grassau, 2013;Petrie, 1976). Petrie's concept of "Idea dominance" (Petrie, 1976: 32) addresses the importance of professionals reducing the emphasis on their particular profession and instead focusing on and highlighting one particular idea so that successful collaboration can be achieved more easily.…”
Section: Identity and Different Modes Of Teamworkmentioning
confidence: 99%
“…Thus, if they are to promote effective collaboration, the collaborating professionals should aim to have greater focus on the same idea rather than their particular professions (Hall & Weaver, 2001;Hall, Weaver, & Grassau, 2013;Petrie, 1976). Petrie's concept of "Idea dominance" (Petrie, 1976: 32) addresses the importance of professionals reducing the emphasis on their particular profession and instead focusing on and highlighting one particular idea so that successful collaboration can be achieved more easily.…”
Section: Identity and Different Modes Of Teamworkmentioning
confidence: 99%
“…Drawing on previous work by Hall, Weaver, and Grassau (2013), a number of theories and approaches can help inform the development of appropriate interventions. These include: (1) The identified patterns of patient-engaged care in this study showed that providers recognized, respected and valued each different perspective brought to the healthcare situation, including those of the patient and family (Engeström, 2005;Petrie, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Ecological systems theory has provided a useful framework from which to consider interprofessional development in the context of a pre-registration IPE initiative and is recommended as a useful addition to the theories within the 'theoretical toolbox' advocated by Hall et al (2013). It provides a means of mapping potential influences on students and tapping into these to create menaingful experiences for those designing interprofessional education opportunities.…”
Section: Insert Figure 2 About Herementioning
confidence: 99%
“…Examples informing contemporary interprofessional education, include the use of cultural-historical activity theory (CHAT) to explore interprofessional collaboration in teams (Bleakley, 2013) and the use of actor network theory (ANT) and complexity theory, as part of a 'theoretical toolbox' to inform the design of interprofessional education initiatives (Hall, Weaver & Grassau, 2013). Whilst CHAT acknowledges that human interaction with the environment is always mediated by culture, tools and signs, ANT focuses on interaction, including inanimate objects as actors.…”
Section: Introductionmentioning
confidence: 99%